Bitwise Logic Using Phase Change Memory Devices Based on the Pinatubo Architecture - Aflalo, Noa; Eilam Yalon; Kvatinsky, Shahar (arXiv.org, 2024)
This paper experimentally demonstrates a near-crossbar memory logic technique called Pinatubo. Pinatubo, an acronym for Processing In Non-volatile memory ArchiTecture for bUlk Bitwise Operations, facilitates the concurrent activation of two or more rows, enabling bitwise operations such as OR, AND, XOR, and NOT on the activated rows. We implement Pinatubo using phase change memory (PCM) and compare our experimental results with the simulated data from the original Pinatubo study. Our findings highlight a significant four-orders of magnitude difference between resistance states, suggesting the robustness of the Pinatubo architecture with PCM technology.